Kinetics, Adsorption and Desorption of Cd(Ii) and Cu(Ii) on Natural Allophane: Effect of Iron Oxide Coating - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Gacitua-Santalices, M; Gacitua-Santalices, M (Elsevier B.V., 2018)
Volcanic soils are a potential source of abundant and low-cost adsorbent materials. Allophane and iron oxides are the main inorganic constituents of Andisols, soils derived from volcanic-ashes abundant in the central and southern continental Chilean territory. The present study aimed to elucidate the effect of free iron oxides on the adsorption of Cd(II) and Cu(II) from aqueous media on natural allophane (NA). Allophane samples consisted of natural allophane, obtained from a Chilean Andisol series, with (NA-FeOx) and without (NA) an iron oxide coating. Material characterisation showed that NA-FeOx was formed by nanometric (100–500 nm) sized spheres coated with an iron oxide layer that most likely consisted of a ferrihydrite-like mineral. On the other hand, NA consisted of aggregates (with particles as big as 1.0 μm) mostly constituted by allophane. The specific surface area of NA-FeOx and NA were ca. 150 and 17 m2 g− 1, respectively, and presented variable surface charge with an isoelectric point of 10.3. and 5.4. From the kinetic studies, equilibrium adsorption was achieved within 60 min and was almost independent of the presence of the iron oxides. Among the kinetic models evaluated, the pseudo-second order model presented a better correlation with the experimental data. The adsorption studies revealed that NA has a greater adsorption capacity of both Cd+ 2 and Cu+ 2 compared to NA-FeOx. Langmuir and Freundlich adsorption models fit the experimental data well, suggesting that the adsorption process is a combination of physical and chemical phenomena. The Freundlich constant (adsorption coefficient, KF) values obtained confirmed the superior affinity of NA active surface sites compared to NA-FeOx. Desorption studies demonstrated that the majority of adsorbed cations were retained by the adsorbent, indicating irreversible chemical adsorption on specific active sites of the adsorbents. © 2018 Elsevier B.V.